2015
DOI: 10.2298/sarh1508391l
|View full text |Cite
|
Sign up to set email alerts
|

Paranoid schizophrenia versus schizoaffective disorder: Neuropsychological aspects

Abstract: In the remission phase, patients with paranoid schizophrenia expressed cognitive disorders in moderate degree, but when it comes to patients with schizoaffective disorder, more massive cognitive, deficits were registered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…The subtypes of schizophrenia are generally not studied separately and studies involving patients with schizophrenia also include patients with schizoaffective disorder (Brazil, 2014a;Leposavic et al, 2015;Mattila et al, 2015). Although it did not seem predictor of treatment response (Mattila et al, 2015), a diagnosis of schizoaffective disorders, compared to that of paranoid schizophrenia, was likely to associated with SGA switching, as found in our study.…”
Section: Comparison With Previous Studiessupporting
confidence: 51%
“…The subtypes of schizophrenia are generally not studied separately and studies involving patients with schizophrenia also include patients with schizoaffective disorder (Brazil, 2014a;Leposavic et al, 2015;Mattila et al, 2015). Although it did not seem predictor of treatment response (Mattila et al, 2015), a diagnosis of schizoaffective disorders, compared to that of paranoid schizophrenia, was likely to associated with SGA switching, as found in our study.…”
Section: Comparison With Previous Studiessupporting
confidence: 51%
“…35 Identifying these biomarkers could contribute to the diagnosis and treatment of schizophrenia. 36 associated with neurocognitive deficits, 37 inhibitory control, intellectual disability, 38,39 working memory, 40 visual and verbal memory, speed processing, attention, 32,[41][42][43][44][45] visual construction, 46 social cognition, 46 theory of mind, [47][48][49] sensory processing, facial recognition deficits, 50 and decision making. 49,51 The identification of these markers could contribute to the diagnosis and treatment of schizophrenia 36 Regarding decision-making in patients with schizophrenia, most studies showed deficiencies in the Iowa Gambling Test (IGT), which suggests a preference for disadvantageous cards, 52 which poses a reduced sensitivity to punishments, being unable to regulate their decision-making to implement practical strategies, even when the probabilities of winning or losing are explicitly revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Paranoid schizophrenia is the most frequent subtype of schizophrenia [4]. Although the subtypes of schizophrenia were eliminated from Diagnostic and Statistical Manual of Mental Disorder (DSM), paranoia remains the most common delusion among patients diagnosed with schizophrenia [5,6].…”
Section: Introductionmentioning
confidence: 99%